COVID-19 and multisystem inflammatory syndrome in children and adolescents (2020)
As severe acute respiratory syndrome coronavirus 2 continues to spread worldwide, there have been increasing reports from Europe, North America, Asia, and Latin America describing children and adolescents with COVID-19-associated multisystem inflammatory conditions. However, the association between multisystem inflammatory syndrome in children and COVID-19 is still unknown. We review the epidemiology, causes, clinical features, and current treatment protocols for multisystem inflammatory syndrome in children and adolescents associated with COVID-19. We also discuss the possible underlying pathophysiological mechanisms for COVID-19- induced inflammatory processes, which can lead to organ damage in paediatric patients who are severely ill. These insights provide evidence for the need to develop a clear case definition and treatment protocol for this new condition and also shed light on future therapeutic interventions and the potential for vaccine development.